A silicon-based negative electrode active material and a lithium battery silicon negative electrode sheet
By covering the nano-silane coupling agent and sulfonated polyimide on the surface of nano-silica, the volume expansion problem of silicon-based anode material when embedded in lithium is solved, and high efficiency and stability are achieved.
Patent Information
- Application Number
- CN202211343811.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-10-31
AI Technical Summary
The silicon-based negative electrode material will expand volumeically when embedded with lithium, resulting in material failure. It is difficult for the prior art to have high first-time Coulomb efficiency and good cycle stability at the same time.
By sequentially coated with aminosilane coupling agent and sulfonated polyimide on the surface of nanosilica, the expansion and powdering effect of nanosilica is effectively suppressed.
The high first-time Coulomb efficiency and good cycle stability of the silicon-based negative electrode active material are achieved, and the structural integrity and volume stability of the material during the embedding/detachment of lithium are enhanced.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon-based negative electrode active material and a lithium battery silicon negative electrode sheet. Background Art
[0002] In recent years, lithium batteries have been widely used and studied compared to traditional secondary batteries such as lead-acid batteries, iron batteries, and nickel-metal hydride batteries due to a series of advantages such as high energy density, long cycle life, safety and pollution-free.
[0003] The performance of key materials for lithium batteries is an important determinant of battery performance, and the development and improvement of negative electrode materials is a global research hotspot. Negative electrode materials such as silicon materials, carbon materials, tin materials, lithium titanate, and metal oxides have been widely studied.
[0004] Among them, silicon negative electrode materials have always been a hot research topic for negative electrode materials for lithium-ion batteries due to their theoretical capacity of up to 4200mAh / g when fully embedded with lithium, low lithium embedding potential, actual specific capacity greater than 3000mAh / g, abundant content in nature, and relatively low raw material prices. However, silicon negative electrode materials have a defect that cannot be ignored, that is, when silicon negative electrodes are embedded with lithium, their volume will expand, and their volume expansion can even reach 360% of the original volume. This inevitable phenomenon of silicon negative electrode materials for lithium-ion batteries usually leads to the failure of negative electrode materials.
[0005] In order to overcome the above defects of silicon negative electrode materials, the prior art either forms alloys with silicon and other inactive metals (such as Fe, Al, Cu, etc.), or evenly disperses silicon into other active or inactive materials to form composite materials (such as Si-C, Si-TiN, etc.). Although these methods can improve the cycle stability of the battery to a certain extent and alleviate the capacity decay of silicon-based negative electrode materials, the high cost hinders its commercialization process, and after multiple cycles, the capacity will begin to decay rapidly. Therefore, it is urgent to find a method for modifying silicon-based negative electrode active materials so that the silicon-based negative electrode active materials have both high first coulomb efficiency and good cycle stability, so as to meet the requirements of power batteries. Summary of the invention
[0006] Based on the problems existing in the background technology, the present invention proposes a silicon-based negative electrode active material and a lithium battery silicon negative electrode sheet. By sequentially coating the surface of nano-silicon with an aminosilane coupling agent and a sulfonated polyimide, the expansion and pulverization effect of nano-silicon is effectively suppressed, so that the silicon-based negative electrode active material has both a higher first coulombic efficiency and better cycle stability.
[0007] The present invention provides a silicon-based negative electrode active material, wherein the silicon-based negative electrode active material uses nano-silicon as a substrate, and an aminosilane coupling agent and a sulfonated polyimide are sequentially coated outside the substrate;
[0008] The sulfonated polyimide has the following general structural formula:
[0009]
[0010] Wherein, m and n are integers greater than 0, R1 is the residue after removing 4 carboxyl groups from tetracarboxylic dianhydride, R2 is the residue after removing 2 amino groups from a diamine having a sulfonic acid group, R3 is the residue after removing 2 carbonyl compounds from an aromatic dicarbonyl compound, and R4 is the residue after removing 2 amino groups from an aromatic diamine.
[0011] Preferably, R1 is one of the following structural formulas:
[0012]
[0013] Preferably, R2 is one of the following structural formulas:
[0014]
[0015] Preferably, R3 is one of the following structural formulas:
[0016]
[0017] Preferably, R4 is one of the following structural formulas:
[0018]
[0019] Preferably, the aminosilane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane or N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0020] Preferably, the amount of the aminosilane coupling agent is 0.1-3wt% of the nano-silicon, and the amount of the sulfonated polyimide is 5-20wt% of the nano-silicon.
[0021] Preferably, the silicon-based negative electrode active material is prepared by the following method:
[0022] S1, mixing an aminosilane coupling agent and nano-silicon to react, to obtain nano-silicon with the surface coated with the aminosilane coupling agent;
[0023] S2, mixing the sulfonated polyimide with the nano-silicon coated with an aminosilane coupling agent to react, thereby obtaining the silicon-based negative electrode active material.
[0024] Preferably, in step S1, the temperature of the mixed reaction is 60-80°C; in step S2, the temperature of the mixed reaction is 80-100°C.
[0025] The present invention also provides a lithium battery silicon negative electrode sheet, which comprises the above silicon-based negative electrode active material.
[0026] In the present invention, the nano-silicon is modified by using an aminosilane coupling agent so that the aminosilane coupling agent is grafted on the surface of the nano-silicon, and then the surface is coated with sulfonated polyimide. The amino group on the aminosilane coupling agent and the sulfonic acid group on the sulfonated polyimide are combined to form an acid-base hydrogen bond, so that the silane coupling agent is used as a bridge to form a tightly combined polyimide coating layer on the surface of the nano-silicon. The imide and amide molecular chain segments of the polyimide coating layer itself have excellent mechanical properties. When the polyimide is coated on the nano-silicon, it not only improves the structural stability of silicon as a negative electrode active material, but also effectively prevents the expansion and pulverization effect of the silicon active material, enhances the structural integrity and volume stability of the silicon active material in the process of inserting / extracting lithium, and improves the cycle stability when used in lithium batteries. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is described in detail below through specific embodiments.
[0028] Example 1
[0029] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0030] (1) Under nitrogen protection, 3.44 g (10 mmol) of 4,4'-diamino-2,2'-biphenyl disulfonic acid was added to m-cresol and stirred to dissolve completely, 2.18 g (10 mmol) of pyromellitic anhydride was added at room temperature and stirred to react for 2 h, and then 2.00 g (10 mmol) of 4,4'-diaminodiphenyl ether and 2.03 g (10 mmol) of terephthaloyl chloride were added in sequence, and the stirring reaction was continued at room temperature for 6 h to obtain a polyamic acid solution; 4.16 g of isoquinoline and 4.52 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred to react for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred to react for 6 h, and then cooled to room temperature and precipitated with excess methanol to precipitate a polymer, and the precipitate was filtered out and rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0031] (2) adding 0.05 g of γ-aminopropyltriethoxysilane to a mixed solution of ethanol and water (V:V = 9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with an aminosilane coupling agent coated on the surface;
[0032] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with the surface coated with an aminosilane coupling agent were added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature was raised to 90° C. and stirred for reaction for 4 h. The obtained reactant was vacuum dried to obtain the silicon-based negative electrode active material.
[0033] Example 2
[0034] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0035] (1) Under nitrogen protection, 3.44 g (10 mmol) of 4,4'-diamino-2,2'-biphenyl disulfonic acid was added to m-cresol and stirred to dissolve completely, 2.94 g (10 mmol) of 3,3',4,4'-biphenyl tetracarboxylic anhydride was added at room temperature and stirred to react for 2 h, and then 2.48 g (10 mmol) of 4,4'-diaminodiphenyl sulfone and 2.03 g (10 mmol) of terephthaloyl chloride were added in sequence, and the stirring reaction was continued at room temperature for 6 h to obtain a polyamic acid solution; 4.16 g of isoquinoline and 4.52 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred to react for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred to react for 6 h, and then cooled to room temperature and precipitated with excess methanol to precipitate a polymer, and the precipitate was filtered out and rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0036] (2) adding 0.05 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane to a mixed solution of ethanol and water (V:V=9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with an aminosilane coupling agent coated on the surface;
[0037] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with the surface coated with an aminosilane coupling agent were added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature was raised to 90° C. and stirred for reaction for 4 h. The obtained reactant was vacuum dried to obtain the silicon-based negative electrode active material.
[0038] Example 3
[0039] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0040] (1) Under nitrogen protection, 3.44 g (10 mmol) of 4,4'-diamino-2,2'-biphenyl disulfonic acid was added to m-cresol and stirred to dissolve completely, 3.22 g (10 mmol) of 3,3',4,4'-benzophenone tetracarboxylic dianhydride was added at room temperature and stirred to react for 2 h, and then 2.16 g (10 mmol) of 4,4'-diaminodiphenyl sulfide and 2.03 g (10 mmol) of terephthaloyl chloride were added in sequence, and the stirring reaction was continued at room temperature for 6 h to obtain a polyamic acid solution; 4.16 g of isoquinoline and 4.52 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred to react for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred to react for 6 h, and then cooled to room temperature and precipitated with excess methanol to precipitate a polymer, and the precipitate was filtered out and rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0041] (2) adding 0.05 g of γ-aminopropyltrimethoxysilane to a mixed solution of ethanol and water (V:V = 9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with an aminosilane coupling agent coated on the surface;
[0042] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with the surface coated with an aminosilane coupling agent were added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature was raised to 90° C. and stirred for reaction for 4 h. The obtained reactant was vacuum dried to obtain the silicon-based negative electrode active material.
[0043] Example 4
[0044] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0045] (1) Under nitrogen protection, 3.44 g (10 mmol) of 4,4'-diamino-2,2'-biphenyl disulfonic acid was added to m-cresol and stirred to dissolve completely, 1.96 g (10 mmol) of 1,2,3,4-cyclobutane tetracarboxylic dianhydride was added at room temperature and stirred to react for 2 h, then 1.08 g (10 mmol) of p-phenylenediamine and 2.03 g (10 mmol) of terephthaloyl chloride were added in sequence, and the stirring reaction was continued at room temperature for 6 h to obtain a polyamic acid solution; 4.16 g of isoquinoline and 4.52 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred to react for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred to react for 6 h, and then cooled to room temperature and precipitated a polymer with excess methanol, the precipitate was filtered out and rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0046] (2) adding 0.05 g of γ-aminopropyltriethoxysilane to a mixed solution of ethanol and water (V:V = 9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with an aminosilane coupling agent coated on the surface;
[0047] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with the surface coated with an aminosilane coupling agent were added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature was raised to 90° C. and stirred for reaction for 4 h. The obtained reactant was vacuum dried to obtain the silicon-based negative electrode active material.
[0048] Example 5
[0049] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0050] (1) Under nitrogen protection, 3.44 g (10 mmol) of 4,4'-diamino-3,3'-biphenyl disulfonic acid was added to m-cresol and stirred to dissolve completely, 2.18 g (10 mmol) of pyromellitic anhydride was added at room temperature and stirred to react for 2 h, and then 2.00 g (10 mmol) of 4,4'-diaminodiphenyl ether and 2.03 g (10 mmol) of terephthaloyl chloride were added in sequence, and the stirring reaction was continued at room temperature for 6 h to obtain a polyamic acid solution; 4.16 g of isoquinoline and 4.52 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred to react for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred to react for 6 h, and then cooled to room temperature and precipitated with excess methanol to precipitate a polymer, and the precipitate was filtered out and rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0051] (2) adding 0.05 g of γ-aminopropyltriethoxysilane to a mixed solution of ethanol and water (V:V = 9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with an aminosilane coupling agent coated on the surface;
[0052] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with the surface coated with an aminosilane coupling agent were added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature was raised to 90° C. and stirred for reaction for 4 h. The obtained reactant was vacuum dried to obtain the silicon-based negative electrode active material.
[0053] Example 6
[0054] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0055] (1) Under nitrogen protection, 3.44 g (10 mmol) of 4,4'-diamino-2,2'-biphenyl disulfonic acid was added to m-cresol and stirred to dissolve completely, 2.18 g (10 mmol) of pyromellitic anhydride was added at room temperature and stirred to react for 2 h, and then 2.00 g (10 mmol) of 4,4'-diaminodiphenyl ether and 2.03 g (10 mmol) of isophthaloyl chloride were added in sequence, and the stirring reaction was continued at room temperature for 6 h to obtain a polyamic acid solution; 4.16 g of isoquinoline and 4.52 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred to react for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred to react for 6 h, and then cooled to room temperature and precipitated a polymer with excess methanol, and the precipitate was filtered out and rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0056] (2) adding 0.05 g of γ-aminopropyltriethoxysilane to a mixed solution of ethanol and water (V:V = 9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with an aminosilane coupling agent coated on the surface;
[0057] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with the surface coated with an aminosilane coupling agent were added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature was raised to 90° C. and stirred for reaction for 4 h. The obtained reactant was vacuum dried to obtain the silicon-based negative electrode active material.
[0058] Comparative Example 1
[0059] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0060] (1) Under nitrogen protection, 3.44 g (10 mmol) of 4,4'-diamino-2,2'-biphenyl disulfonic acid was added to m-cresol and stirred to dissolve completely, 2.18 g (10 mmol) of pyromellitic anhydride was added at room temperature and stirred to react for 2 h, and then 2.00 g (10 mmol) of 4,4'-diaminodiphenyl ether and 2.03 g (10 mmol) of terephthaloyl chloride were added in sequence, and the stirring reaction was continued at room temperature for 6 h to obtain a polyamic acid solution; 4.16 g of isoquinoline and 4.52 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred to react for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred to react for 6 h, and then cooled to room temperature and precipitated with excess methanol to precipitate a polymer, and the precipitate was filtered out and rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0061] (2) adding 0.05 g of γ-glycidyloxypropyltrimethoxysilane to a mixed solution of ethanol and water (V:V = 9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with a silane coupling agent coated on the surface;
[0062] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with a silane coupling agent coated on the surface are added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature is raised to 90° C. and stirred for reaction for 4 hours. The obtained reactant is vacuum dried to obtain the silicon-based negative electrode active material.
[0063] Comparative Example 2
[0064] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0065] (1) Under nitrogen protection, 1.84 g (10 mmol) of 4,4'-diaminobiphenyl was added to m-cresol and stirred to dissolve completely, 2.18 g (10 mmol) of pyromellitic anhydride was added at room temperature and stirred to react for 2 h, and then 2.00 g (10 mmol) of 4,4'-diaminodiphenyl ether and 2.03 g (10 mmol) of terephthaloyl chloride were added in sequence, and the stirring reaction was continued for 6 h at room temperature to obtain a polyamic acid solution; 4.16 g of isoquinoline and 4.52 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred to react for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred to react for 6 h. After cooling to room temperature, the polymer was precipitated with excess methanol, the precipitate was filtered out, and then rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0066] (2) adding 0.05 g of γ-aminopropyltriethoxysilane to a mixed solution of ethanol and water (V:V = 9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with an aminosilane coupling agent coated on the surface;
[0067] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with the surface coated with an aminosilane coupling agent were added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature was raised to 90° C. and stirred for reaction for 4 h. The obtained reactant was vacuum dried to obtain the silicon-based negative electrode active material.
[0068] Comparative Example 3
[0069] A silicon-based negative electrode active material, the preparation method of which comprises the following steps:
[0070] (1) Under nitrogen protection, 3.44 g (10 mmol) of 4,4'-diamino-2,2'-biphenyl disulfonic acid was added to m-cresol and stirred to dissolve completely, and 2.18 g (10 mmol) of pyromellitic anhydride was added at room temperature and stirred for 2 h to obtain a polyamic acid solution; 2.08 g of isoquinoline and 2.26 g of acetic anhydride were added to the polyamic acid solution, and the mixture was stirred for 1 h at room temperature, and then the mixture was heated to 80° C. and stirred for 4 h. After cooling to room temperature, the polymer was precipitated with excess methanol, the precipitate was filtered out, and then rinsed with methanol, and dried to obtain a sulfonated polyimide;
[0071] (2) adding 0.05 g of γ-aminopropyltriethoxysilane to a mixed solution of ethanol and water (V:V = 9:1) and stirring to dissolve completely, then adding 4 g of nano-silicon powder (average particle size of 50 nm) and stirring to mix evenly, then heating to 70° C. and stirring to react for 12 h, and after vacuum drying the obtained reactant, obtaining nano-silicon with an aminosilane coupling agent coated on the surface;
[0072] (3) 0.5 g of the above-mentioned sulfonated polyimide and 4 g of the above-mentioned nano-silicon with the surface coated with an aminosilane coupling agent were added to N-methylpyrrolidone, and after being stirred and dispersed completely, the temperature was raised to 90° C. and stirred for reaction for 4 h. The obtained reactant was vacuum dried to obtain the silicon-based negative electrode active material.
[0073] 1 g of the silicon-based negative electrode active material prepared in the above embodiments and comparative examples, 0.2 g of acetylene black (conductive aid), and 0.3 g of sodium polyacrylate binder were added to deionized water and stirred to obtain a negative electrode slurry. The negative electrode slurry was coated on a copper foil current collector with a thickness of 10 μm, dried at 180° C. for 2 h, and rolled to obtain a negative electrode sheet; a lithium sheet was used as a counter electrode, Celgard 2400 was used as a separator, and a mixed solution of 1 mol / L LiPF6 of ethylene carbonate (EC) and diethyl carbonate (EMC) (v / v=1:1) was used as an electrolyte solution, and a CR2032 button battery was assembled in a glove box filled with argon.
[0074] The above battery was subjected to constant current charge and discharge test at room temperature. Specifically, the button battery was subjected to charge and discharge test in the voltage range of (3-0.01) V at a constant current of 0.5C. The test results are shown in Table 1 below.
[0075] Table 1 Cyclic performance of the silicon-based negative electrode active materials described in Examples and Comparative Examples
[0076]
[0077]
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A silicon-based negative electrode active material, characterized in that: The silicon-based negative electrode active material is based on nano-silicon, and an aminosilane coupling agent and a sulfonated polyimide are sequentially coated outside the base; The sulfonated polyimide has the following general structural formula: Wherein, m and n are integers greater than 0, R1 is the residue after removing four carboxyl groups from tetracarboxylic dianhydride, R2 is the residue after removing two amino groups from a diamine having a sulfonic acid group, R3 is the residue after removing two carbonyl compounds from an aromatic dicarbonyl compound, and R4 is the residue after removing two amino groups from an aromatic diamine; The silicon-based negative electrode active material is prepared by the following method: S1, mixing an aminosilane coupling agent and nano-silicon to react, to obtain nano-silicon with the surface coated with the aminosilane coupling agent; S2, mixing the sulfonated polyimide with the nano-silicon coated with an aminosilane coupling agent to react, thereby obtaining the silicon-based negative electrode active material.
2. The silicon-based negative electrode active material according to claim 1, characterized in that: R1 is one of the following structural formulas: 。 3. The silicon-based negative electrode active material according to claim 1 or 2, characterized in that: R2 is one of the following structural formulas: 。 4. The silicon-based negative electrode active material according to claim 1 or 2, characterized in that: R3 is one of the following structural formulas: 。 5. The silicon-based negative electrode active material according to claim 1 or 2, characterized in that: R4 is one of the following structural formulas: 。 6. The silicon-based negative electrode active material according to claim 1 or 2, characterized in that: The aminosilane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane or N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
7. The silicon-based negative electrode active material according to claim 1 or 2, characterized in that: The amount of the aminosilane coupling agent used is 0.1-3wt% of the nano-silicon, and the amount of the sulfonated polyimide used is 5-20wt% of the nano-silicon.
8. The silicon-based negative electrode active material according to claim 1, characterized in that: In step S1, the temperature of the mixed reaction is 60-80°C; in step S2, the temperature of the mixed reaction is 80-100°C.
9. A lithium battery silicon negative electrode sheet, characterized in that: It comprises the silicon-based negative electrode active material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Sulfonated polyimide binder, electrode plate and lithium ion battery
CN111777984A
Negative electrode active material of polyamide acid modified nano silicon and preparation method of negative electrode active material
CN113594429A
Silicon negative electrode material, secondary battery, and device
CN114709390A